The lion, the witch and the wardrobe - Lewis, C. S. (HarperCollins Publishers UK, 2010)
Introducing the second book of the newly designed narnia classics. Perfect for those seeking a contemporary take on the chronicles of narnia.the most loved of all the chronicles, this wonderful tale can be enjoyed again and again. Lucy steps into the professor's wardrobe but steps out again into a snowy forest. She's stumbled upon the magical world of narnia, land of unicorns, centaurs, fauns! and the wicked white witch, who terrorises all. Lucy soon realises that narnia, and in particular aslan, the great lion, needs her help if the country's creatures are ever going to be free again.